Carbon material, its manufacturing method, and fuel cell
Patent Information
- Application Number
- JP2023554309
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-27
- Filing Date
- 2023-04-26
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2043-04-26
AI Technical Summary
【0043】 本出願の技術的解決策は少なくとも以下の有益な効果を有する。
Smart Images

Figure 0007638027000010 
Figure 0007638027000011 
Figure 0007638027000012
Abstract
Description
[Technical field]
[0001] (Related Applications) This application claims priority to a Chinese patent application entitled "Carbon material, its preparation method, and fuel cell," filed with the China Patent Office on September 27, 2022, application number 202211184403.7, the entire contents of which are incorporated herein by reference.
[0002] (Technical field) The present application relates to the technical field of fuel cells, and in particular to carbon materials and methods for their preparation, as well as fuel cells. [Background technology]
[0003] Existing fuel cells are mainly composed of multiple cell units with gas diffusion layers, which are composed of microporous layers and substrates. Among them, the microporous layer is mainly composed of highly structured carbon materials, and is responsible for gas permeation, discharge, and electron transfer in fuel cells. The physical and chemical properties of the microporous layer, such as hydrophilicity and hydrophobicity, electrical conductivity, and pore structure, directly affect the performance of the cell. The use environment of the microporous layer is high potential and high humidity, and the carbon material is prone to electrochemical corrosion. After the carbon material of the microporous layer is corroded, the hydrophilicity and hydrophobicity and pore structure of the material change, the drainage and air transfer function is reduced, the contact resistance between the interfaces of the parts is increased, and the performance degradation of the battery is accelerated. Therefore, the electrochemical stability of the carbon material used in the microporous layer determines the operating life of the battery to a certain extent.
[0004] Existing microporous layers mainly use commercially available conductive carbon blacks such as furnace black, acetylene black, and cobalt black as their main materials. However, the particles of these types of carbon black materials have many interface defects and are prone to electrochemical corrosion, which accelerates the degradation of carbon materials.
[0005] Therefore, there is a demand for carbon materials that exhibit good functionality in gas transport, drainage, and electron transport in fuel cells, as well as high resistance to electrochemical corrosion, and that can improve the battery life. Summary of the Invention [Problem to be solved by the invention]
[0006] In view of these points, the present application provides a carbon material having fewer areas of the surface of carbon particles that are susceptible to corrosion, high corrosion resistance, and capable of effectively improving the service life of the carbon material, as well as a method for preparing the same, and a fuel cell. [Means for solving the problem]
[0007] According to a first aspect, an embodiment of the present application provides a carbon material, the carbon material is made of carbon particles, the surface of the carbon particles includes a plurality of connected carbon crystal particles, and there is a grain boundary between two adjacent carbon crystal particles; The grain boundary density p of the surface of the carbon particle is 1≦p≦15; The grain boundary density is determined by the following measurement method: 20 carbon particles were randomly selected and measured by Raman spectroscopy. The peak area I of the carbon characteristic peak of the carbon particles was D and the peak area of the graphite characteristic peak I G Ratio I D / I G The value of is Rn, n = 1, 2, 3 ... 20, and the I of 20 parts of carbon particles D / I G The average value of is R, Grain boundary density
number
[0008] In some embodiments, the carbon particles are spherical or approximate spheres.
[0009] In some embodiments, the carbon particles have an average particle size D such that 20 nm≦D≦200 nm.
[0010] In some embodiments, the carbon crystal particles are formed by stacking carbon layers.
[0011] In some embodiments, the average particle size La of the carbon crystal particles is 3 nm≦La≦30 nm.
[0012] In some embodiments, the grain boundary density p of the surface of the carbon particles is 1≦p≦6.5.
[0013] In some embodiments, a powder X-ray diffraction test shows that the crystal surface spacing of the graphite phase {002} of the carbon material is d 002 nm, 2.5 kN / cm 2 The powder conductivity of the carbon material under pressure is σS / cm and σ / d 002 ≧2*10 8 S / cm 2 It is.
[0014] In some embodiments, the graphite phase of the carbon material has a {002} crystal surface spacing of d 002 nm, and 0.338≦d 002 ≦0.345.
[0015] In some embodiments, 2.5 kN / cm 2 The powder conductivity of the carbon material under pressure is σS / cm, and σ≧7.
[0016] In some embodiments, the carbon material has a porosity of ≧60%.
[0017] In some embodiments, the powder contact angle of the carbon material is between 120° and 155°.
[0018] In some embodiments, the specific surface area of the carbon material is 30 m 2 / g~250m 2 / g.
[0019] In some embodiments, the oil absorption of the carbon material is from 100 mL / 100 g to 450 mL / 100 g.
[0020] In some embodiments, the carbon material has an average particle size of 0.1 μm to 10 μm.
[0021] According to a second aspect, an embodiment of the present application provides a method for preparing a carbon material, the method comprising: A step of carbonizing the mixed material containing the carbon black material and the defect repair agent at 1800 ° C to 3000 ° C and then performing a shaping process; and performing a surface modification treatment on the shaping treatment product in an atmosphere containing a modifying gas to obtain a carbon material.
[0022] In some embodiments, the boiling point of the defect repair agent is 50°C to 400°C.
[0023] In some embodiments, the defect repair agent comprises a volatile organic compound and / or a semi-volatile organic compound.
[0024] In some embodiments, the defect repair agent comprises a volatile organic compound, the volatile organic compound comprising at least one of camphor, phenol, o-phthalaldehyde, isophthalaldehyde, terephthalaldehyde, p-benzoquinone, benzoic acid, palmitol, aminoquinoline, and naphthalene.
[0025] In some embodiments, the defect repair agent comprises a semi-volatile organic compound, the semi-volatile organic compound comprising at least one of benzenediol, phthalic acid, and anthracene solvate with isophthalaldehyde.
[0026] In some embodiments, before subjecting the mixed material containing the carbon black material and the defect repairing agent to a carbonization treatment at 1800° C. to 3000° C., the method further includes a step of shaping the defect repairing agent, and mixing the shaped repairing agent and the carbon black material to obtain the mixed material.
[0027] In some embodiments, the average particle size of the defect repairing agent is 0.1 μm to 1 μm.
[0028] In some embodiments, the mass ratio of the carbon black material to the defect repair agent is 10:(0.1 to 2).
[0029] In some embodiments, the carbon black material has an average particle size of from 20 nm to 200 nm.
[0030] In some embodiments, the oil absorption of the carbon black material is between 100 mL / 100 g and 450 mL / 100 g.
[0031] In some embodiments, the carbon black material has a carbon characteristic peak I as measured by Raman spectroscopy. D and graphite characteristic peak I G and I D / I G <=2.0.
[0032] In some embodiments, 2.5 kN / cm 2 The powder conductivity of the carbon black material under pressure is σ≧8 S / cm.
[0033] In some embodiments, the carbonization treatment time is 0.1 hours to 3 hours.
[0034] In some embodiments, the temperature increase rate in the carbonization treatment is 2° C. / min to 30° C. / min.
[0035] In some embodiments, the shaping process includes at least one of a ball mill, a sand mill, a roller mill, an agitator mill, a turn mill, and a planetary mill.
[0036] In some embodiments, the method further comprises sieving the shaping product prior to subjecting the shaping product to a surface modification treatment.
[0037] In some embodiments, the modified gas comprises at least one of carbon dioxide, air, water vapor, oxygen, nitrogen, and ammonia.
[0038] In some embodiments, the atmosphere further comprises an inert gas, the inert gas comprising at least one of argon, neon, helium, and krypton.
[0039] In some embodiments, the volume ratio of the modified gas to the inert gas in the atmosphere is (0.5-10):10.
[0040] In some embodiments, the temperature of the surface modification treatment is 400°C to 1700°C, and the temperature of the surface modification treatment is preferably 500°C to 1200°C.
[0041] In some embodiments, the temperature increase rate in the surface modification treatment is 2° C. / min to 30° C. / min.
[0042] According to a third aspect, the present application provides a fuel cell, the fuel cell comprising a plurality of cell units having gas diffusion layers, the gas diffusion layers comprising the carbon material described above or a carbon material prepared by the preparation method described above. Effect of the Invention
[0043] The technical solution of the present application has at least the following beneficial effects:
[0044] First, the carbon material provided by the present application has a smaller grain boundary density between carbon crystal particles on the surface of the carbon material particles, which reduces the number of sites on the surface of the carbon particles that are prone to corrosion, and can effectively improve the service life of the carbon material. The smaller the surface grain boundary density of the carbon particles, the better the hydrophobicity, and the less likely the moisture generated by the reaction is to collect in the pores of the carbon material, so that the microporous layer made of this material and its pore structure maintain the gas conduction ability, and improve the battery performance under conditions of high humidity and high current density. In addition, the carbon material has high electrical conductivity and high graphitization degree. The higher the electrical conductivity of the carbon material, the higher the electron transfer performance of the carbon material and the lower the power loss, and the higher the graphitization degree of the carbon material, the higher the corrosion resistance of the material. As a result, the gas diffusion layer made of this material has high electrochemical conversion efficiency under high current density and also has the characteristics of a long service life.
[0045] Next, the preparation method provided by the present application is to carry out a carbonization treatment at 1800 ° C ~ 3000 ° C of the mixed material containing the carbon black material and the defect repair agent, during the ultra-high temperature carbonization treatment, the defect repair agent can decompose to generate a carbon radical or carbene structure, which is a typical electron-deficient neutral active intermediate, and precipitate on the surface of the carbon particles to repair the defects on the carbon particle surface, thereby obtaining carbon particles with a low grain boundary density on the surface, contributing to obtaining a carbon material with high graphitization, high conductivity and high durability, and then, by a shaping treatment, the particle size of the carbon material can be reduced, contributing to the preparation of a gas diffusion layer with a flat surface of the carbon material and a uniformly distributed microporous layer. By carrying out a surface modification treatment on the product after the shaping treatment, the structural order of the carbon material surface can be improved, and the chemical and electrochemical corrosion resistance can be improved. The whole preparation process is simple, and can improve the high electrical conductivity performance and high hydrophobic durability performance of the material, improve the service life of the carbon material, and reduce the preparation cost. [Brief description of the drawings]
[0046] [Figure 1] FIG. 2 is a structural schematic diagram showing the grain boundary state between carbon crystal particles in the carbon material provided by the present application. [Diagram 2] FIG. 1 is a structural schematic diagram of a carbon material provided by an embodiment of the present application. [Diagram 3] 1 is a schematic flow chart of a carbon material preparation method provided by an embodiment of the present application. [Figure 4] FIG. 2 is a thermogravimetric loss diagram of the carbon materials of Examples 1 and 3 and Comparative Example 1 of the present application. [Diagram 5] FIG. 2 is an electrochemical potentiostatic polarization curve diagram of the gas diffusion layers of the fuel cells prepared by the carbon material coatings of Examples 1 and 3 and Comparative Example 1 of the present application. [Figure 6] FIG. 2 is a linear diagram showing the corrosion current growth rate of the corresponding carbon material obtained by linear fitting of the electrochemical potentiostatic polarization curves of the diffusion layers prepared by the carbon material coatings of Examples 1 and 3 and Comparative Example 1 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0047] The following describes the embodiments of the present application. However, it should be noted that those skilled in the art can make many improvements and modifications without departing from the principles of the embodiments of the present application, and these improvements and modifications fall within the scope of protection of the embodiments of the present application.
[0048] The present application provides a carbon material, and FIG. 1 is a schematic structural diagram showing a grain boundary state between carbon crystal particles in the carbon material provided by the present application. As shown in FIG. 1, the carbon material is composed of carbon particles, the surface of the carbon particle includes a plurality of connected carbon crystal particles, and there is a grain boundary between two adjacent carbon crystal particles; The grain boundary density p on the surface of the carbon particle is 1≦p≦15; The grain boundary density is determined by the following measurement method: 20 carbon particles were randomly selected and measured by Raman spectroscopy. The peak area I of the carbon characteristic peak of the carbon particles was D and the peak area of the graphite characteristic peak I G Ratio I D / I G The value of R n and n=1, 2, 3...20, and 20 parts of carbon particles I D / I G The average value of is R, Grain boundary density
number
[0049] In the above solution, the smaller the grain boundary density between the carbon crystal particles on the surface of the carbon material particles, the fewer the sites on the surface of the carbon particles that are prone to corrosion, which effectively improves the service life of the carbon material; the smaller the surface grain boundary density of the carbon particles, the better the hydrophobicity, and the less likely the moisture generated by the reaction is to collect in the pores of the carbon material, which maintains the gas conduction ability of the microporous layer made of this material and its pore structure, thereby improving the battery performance under conditions of high humidity and high current density. In addition, the carbon material has high electrical conductivity and high graphitization degree. The higher the electrical conductivity of the carbon material, the higher the electron transfer performance of the carbon material and the lower the power loss, and the higher the graphitization degree of the carbon material, the higher the corrosion resistance performance of the material. As a result, the gas diffusion layer made of this material has the characteristics of high electrochemical conversion efficiency under high current density and long service life.
[0050] As can be appreciated, the carbon particles are primary particles, and the primary particles can aggregate to form secondary particles.
[0051] In some embodiments, the peak area I of the carbon characteristic peak of the carbon particle D and the peak area of the graphite characteristic peak I G The ratio of is 0.15≦I D / I G ≦1.5.
[0052] In some embodiments, the grain boundary density p is specifically, but not limited to, 1, 1.5, 2, 2.5, 3, 3.5, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15. Preferably, 1≦p≦10. As can be understood, the corrosion of carbon materials usually starts along the grain boundary positions on the surface of carbon particles. The smaller the grain boundary density on the surface of carbon particles, the fewer sites prone to corrosion on the surface, and the longer the service life of the carbon material. Preferably, the grain boundary density p, 1≦p≦6.5. Because there are many grain boundaries on the surface of carbon black materials in the prior art, it is difficult to achieve a football-shaped alkene structure state that is completely free of grain boundaries.
[0053] Grain boundary density
number
[0054] The average particle size of the carbon crystal particles can be measured by Raman spectroscopy, and the peak area I of the carbon characteristic peak of the carbon particles can be calculated. D and the peak area of the graphite characteristic peak I G Ratio I D / I G The average value R of the Raman peak intensity and the average particle size La of the carbon crystal particles are calculated from the Raman peak intensity ratio of carbon, and are La = 4.4 / R (Raman laser wavelength λ = 514 nm).
[0055] In some embodiments, as shown in FIG. 2, the average particle size La of the carbon crystal particles is 3 nm≦La≦30 nm, specifically, 3 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, or 30 nm, etc., and is not limited to the listed values, and other values not listed within this range are also applicable. By controlling the average particle size of the carbon crystal particles within the above range, the grain boundary density between the carbon crystal particles can be reduced, defects can be reduced, and the corrosion resistance of the carbon material can be improved. Preferably, 5 nm≦La≦20 nm.
[0056] In some embodiments, the carbon particles are spherical or approximate spheres.
[0057] In some embodiments, the carbon crystal particles are formed by stacking of carbon layers.
[0058] Since the surface of a carbon particle contains multiple connected carbon crystal particles, the external surface area of the carbon particle is obtained by adding up the surface areas of each carbon crystal particle. In other words, the number of carbon crystal particles n = external surface area of carbon particle / surface area of carbon crystal particle, and the calculation formula is shown as follows.
number
[0059] Grain boundary density of carbon particles=(number of carbon crystal particles*average surface crystal particle circumference / 2) / average single particle circumference, and the calculation formula is given by the following formula.
number
[0060] In some embodiments, the average particle size D of the carbon particles is 20 nm ≦ D ≦ 200 nm, specifically, 20 nm, 50 nm, 60 nm, 80 nm, 90 nm, 100 nm, 120 nm, 150 nm, 180 nm, 190 nm, or 200 nm, etc., and is not limited to the listed values, and other values not listed within this range are also applicable. By controlling the average particle size of the carbon particles within the above range, a carbon material with a pore structure having good drainage and gas permeability is obtained, a gas diffusion layer with a flat surface is formed, and the contact resistance between the gas diffusion layer and the catalyst layer is reduced. Preferably, 30 nm ≦ D ≦ 100 nm.
[0061] In some embodiments, the particle size D of the carbon material 90 ≦200 μm, specifically, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 100 μm, 150 μm or 200 μm, and of course, may be other values within the above range, but are not limited thereto. 90 ≦100μm. D of carbon materials 90 If the particle size is too large, it does not contribute to the formation of a gas diffusion layer with a flat surface. Carbon particles of an appropriate size can form a gas diffusion layer with a flat surface and reduce the contact resistance between the gas diffusion layer and the catalyst layer.
[0062] In some embodiments, the carbon materials have high graphitic phase crystallinity and high conductive properties.
[0063] In some embodiments, the results of a powder X-ray diffraction test show that the crystal surface spacing of the graphite phase {002} of the carbon material is d 002 nm, 2.5 kN / cm 2 The powder conductivity of carbon materials under pressure is σ(S / cm) and σ / d 002 ≧2*10 8 S / cm 2The ratio of powder conductivity to crystal surface spacing is used to express the high graphitization degree and high electrical conductivity properties of carbon materials. As can be understood, the higher the graphitization degree of the carbon material, the higher the corrosion resistance performance of the carbon material, the better the electrical conductivity performance of the carbon material, the stronger the electron transport performance of the carbon material, and the lower the power loss. Preferably, σ / d 002 ≧3*10 8 S / cm 2 Therefore, by controlling the powder conductivity and the crystal surface spacing of the carbon material of the present application within the above ranges, the carbon material can achieve both high electrical conductivity characteristics and a longer service life.
[0064] Here, the graphite phase {002} crystal plane diffraction peak angle of the carbon material is measured by a powder X-ray diffraction test, and the {002} crystal surface spacing d of the carbon material is calculated by the Bragg equation 2dsinθ=nλ. 002 Calculate the value of In some embodiments, the {002} crystal surface spacing d 002 0.338 nm ≦ d 200 ≦0.345 nm, specifically, 0.338 nm, 0.339 nm, 0.340 nm, 0.341 nm, 0.342 nm, 0.343 nm, 0.344 nm, or 0.345 nm, etc., and are not limited to the recited values, and other unrecited values within this range are equally applicable. The smaller the crystal surface spacing of the carbon particles, the higher the crystallinity of the carbon material.
[0065] In some embodiments, the powder conductivity measurement results in a powder conductivity σ of the carbon material being σ≧7 S / cm, specifically, 7 S / cm, 7.5 S / cm, 7.9 S / cm, 8.5 S / cm, 8.9 S / cm, 9.5 S / cm, 10.0 S / cm, or 11.0 S / cm, etc., but not limited to the listed values, when a pressure of 2.5 kN is applied to the carbon material. The higher the conductivity of the carbon material, the lower the electron transport resistance of the material, and the higher the battery performance of the gas diffusion layer made of the carbon material.
[0066] In some embodiments, the porosity of the carbon material is ≧60%, specifically, but not limited to, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%. The higher the porosity of the carbon material, the more it contributes to the diffusion of reaction gases in the gas diffusion layer. Preferably, the porosity of the carbon material is ≧80%.
[0067] In some embodiments, the powder contact angle of the carbon material is 120° to 155°, specifically, but not limited to, 120°, 125°, 130°, 135°, 140°, 145°, 150°, or 155°. By controlling the powder contact angle of the carbon material within the above range, the hydrophobic performance of the carbon material is improved, moisture generated by the reaction is less likely to collect in the pores of the carbon material, and corrosion of the carbon particles is also avoided, which contributes to improving the service life of the carbon material.
[0068] In some embodiments, the specific surface area of the carbon material is 30 m 2 / g~250m 2 / g, and optionally, the specific surface area ratio of the carbon material is 30 m 2 / g, 40m 2 / g, 60m 2 / g, 80m 2 / g, 100m 2 / g, 120m 2 / g, 140m 2 / g, 160m 2 / g, 180m 2 / g, 200m 2 / g or 250m 2 / g, etc., but are not limited to these. As can be understood, by controlling the specific surface area of the carbon material within the above range, the carbon material can have better gas permeation and drainage performance.
[0069] In some embodiments, the oil absorption of the carbon material is 100mL / 100g to 450mL / 100g, specifically, but not limited to, 100mL / 100g, 200mL / 100g, 250mL / 100g, 300mL / 100g, 350mL / 100g, 400mL / 100g or 450mL / 100g. The higher the oil absorption of the carbon material, the better the gas permeation and drainage performance of the carbon material. From the viewpoint of the mass transfer performance of the material, preferably, the oil absorption of the carbon material is 250mL / 100g to 400mL / 100g.
[0070] In some embodiments, the average particle size of the carbon material is 0.1 μm to 10 μm, such as, but not limited to, 0.1 μm, 0.2 μm, 0.4 μm, 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 5 μm, 8 μm, or 10 μm.
[0071] In addition, the present application further provides a method for preparing a carbon material, as shown in FIG. 3, comprising the following steps: Step S1: A mixed material containing a carbon black material and a defect repairing agent is carbonized at 1800°C to 3000°C, and then shaped; In step S2, the product of the shaping treatment is subjected to a surface modification treatment in an atmosphere containing a modifying gas to obtain the carbon material.
[0072] In the above solution, the mixed material containing the carbon black material and the defect repair agent is carbonized at 1800℃~3000℃, during the ultra-high temperature carbonization, the defect repair agent can decompose to generate carbon radicals or carbene structures, which are typical electron-deficient neutral active intermediates, and precipitate on the surface of the carbon particles to repair the defects on the carbon particle surface, thereby obtaining carbon particles with low grain boundary density on the surface, contributing to obtaining a carbon material with high graphitization, high conductivity and high durability, and then, by the shaping treatment, the particle size of the carbon material can be reduced, contributing to the preparation of a gas diffusion layer with a flat surface of the carbon material and a uniformly distributed microporous layer. By performing a surface modification treatment on the product after the shaping treatment, the structural order of the carbon material surface can be improved and the chemical and electrochemical corrosion resistance can be improved. The whole preparation process is simple, which can improve the high electrical conductivity performance and high hydrophobic durability performance of the material, improve the service life of the carbon material, and reduce the preparation cost.
[0073] This solution will be described in detail below.
[0074] Prior to step S1, the method comprises: The method further includes a step of shaping the defect repairing agent, and mixing the shaped repairing agent with the carbon black material to obtain a mixed material.
[0075] In some embodiments, the shaping method of the defect repairing agent is polishing, the polishing time of the defect repairing agent is 1 h to 6 h, and the average particle diameter of the defect repairing agent after shaping reaches 0.1 μm to 1 μm.
[0076] In some embodiments, the polishing time is specifically, but not limited to, 1h, 2h, 3h, 4h, 5h, or 6h, and may be other values within the above range.Specific polishing methods include, but are not limited to, ball milling, mechanical polishing, and the like.
[0077] In some embodiments, the average particle size of the defect repairing agent after shaping is specifically 0.1 μm, 0.3 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, but is not limited thereto. If the particle size of the particles is at the 100 nano level, the degree of dispersion of the defect repairing agent in the carbon black material can be increased, and the defect repairing agent can be volatilized more slowly and diffused uniformly. If the particle size of the repairing agent is small, it will volatilize quickly during the temperature rise process and lose the function of the repairing agent, and if the particle size of the repairing agent is large, it will be difficult to disperse uniformly and the repairing effect will be weak.
[0078] In some embodiments, the boiling point of the defect repairing agent is 50°C to 400°C, specifically, 50°C, 80°C, 100°C, 120°C, 150°C, 180°C, 200°C, 250°C, 260°C, 280°C, 320°C, 380°C or 400°C, etc., and of course, other values within the above range may be used, but are not limited thereto. The defect repairing agent has a low boiling point and is easily thermally decomposed during the high-temperature carbonization process, and the carbon radical and / or carbene structure is a typical electron-deficient neutral active intermediate, which can be deposited on the surface of the carbon particles to repair the defects on the carbon particle surface.
[0079] In some embodiments, the defect repair agent includes volatile organic compounds (VOCs) and / or semi-volatile organic compounds (SVOCs), where the boiling point of the volatile organic compounds (VOCs) is 50°C to 260°C, and the boiling point of the semi-volatile organic compounds (SVOCs) is 240°C to 400°C.
[0080] Specifically, the boiling points of volatile organic compounds (VOCs) may be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 210°C, 230°C, 250°C or 260°C, and of course may be other values within the above ranges, but are not limited to these.
[0081] Specifically, the boiling points of semi-volatile organic compounds (VOCs) may be 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 350°C, 360°C, 370°C, 390°C, or 400°C, and may of course be other values within the above ranges, but are not limited thereto.
[0082] In some embodiments, the defect repair agent comprises a volatile organic compound, the volatile organic compound comprising at least one of camphor, phenol, o-phthalaldehyde, isophthalaldehyde, terephthalaldehyde, p-benzoquinone, benzoic acid, palmitol, aminoquinoline, and naphthalene.
[0083] In some embodiments, the defect repair agent comprises a semi-volatile organic compound, the semi-volatile organic compound comprising at least one of benzenediol, phthalic acid, and anthracene solvate with isophthalaldehyde.
[0084] In some embodiments, the mixing process of the defect repair agent and the carbon black material after shaping includes at least one of mechanical mixing and stirring mixing. Illustratively, a mixer is used for mixing to improve the homogeneity of the mixed material.
[0085] In some embodiments, the time for the mixing treatment is 0.5 h to 3 h, specifically, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, or 3 h, etc., and of course may be other values within the above range, but is not limited thereto.
[0086] In step S1, a mixed material containing a carbon black material and a defect repairing agent is carbonized at 1800°C to 3000°C, and then shaped.
[0087] In some embodiments, the mass ratio of the carbon black material to the defect repairing agent is 10:(0.1-2), specifically, but not limited to, 10:0.1, 10:0.3, 10:0.5, 10:0.8, 10:1, 10:1.2, 10:1.5, 10:1.8, or 10:0.2, etc., and may of course be other values within the above range. During the carbonization process, the carbon radicals and / or carbene structures formed by the thermal decomposition of the defect repairing agent can be deposited on the surface of the carbon particles to repair defects on the carbon particle surface.
[0088] In some embodiments, the average particle size of the carbon black material is between 20 nm and 200 nm, such as 20 nm, 50 nm, 60 nm, 80 nm, 90 nm, 100 nm, 120 nm, 150 nm, 180 nm, 190 nm, or 200 nm, but is not limited to the recited values; other unrecited values within this range are equally applicable.
[0089] In some embodiments, the oil absorption of the carbon black material is 100 mL / 100 g to 450 mL / 100 g, specifically, but not limited to, 100 mL / 100 g, 200 mL / 100 g, 250 mL / 100 g, 300 mL / 100 g, 350 mL / 100 g, 400 mL / 100 g, or 450 mL / 100 g. In view of the mass transfer performance of the material, preferably, the oil absorption of the carbon black material is 300 mL / 100 g to 450 mL / 100 g.
[0090] In some embodiments, the carbon black material has a carbon characteristic peak I as measured by Raman spectroscopy. D and graphite characteristic peak I G I D / I G ≦2.0, specifically, for example, 2.0, 1.8, 1.6, 1.5, 1.4, 1.2, 1.0, 0.8 or 0.6, but not limited thereto.
[0091] In some embodiments, 2.5 kN / cm 2The powder conductivity σ of the carbon black material under pressure is σ≧8 S / cm, specifically, but not limited to, 8 S / cm, 9 S / cm, 10 S / cm, 11 S / cm, 12 S / cm, 13 S / cm, 14 S / cm or 15 S / cm.
[0092] In some embodiments, the carbonization temperature is 1800°C to 3000°C, specifically 1800°C, 1900°C, 2000°C, 2200°C, 2300°C, 2350°C, 2400°C, 2500°C, 2600°C, 2700°C, 2800°C, or 3000°C, and may of course be other values within the above range, but are not limited thereto. A high carbonization temperature contributes to highly graphitizing the carbon material, forming carbon crystal particles connected in a sheet shape, and reducing the grain boundary density on the surface of the carbon material.
[0093] In some embodiments, the carbonization time is 0.1h to 12h, specifically, 0.1h, 0.2h, 0.5h, 1h, 2h, 4h, 6h, 8h, 10h or 12h, etc., and of course, may be other values within the above range, but are not limited thereto. The carbon material formed by sufficient carbonization has high crystallinity and high graphitization characteristics.
[0094] In some embodiments, the heating rate of the carbonization treatment is 2°C / min to 30°C / min, for example, 2°C / min, 3°C / min, 5°C / min, 10°C / min, 15°C / min, 20°C / min, 25°C / min, or 30°C / min, and of course may be other values within the above range, but is not limited to these.
[0095] In some embodiments, the temperature drop rate after carbonization is 1° C. / min to 20° C. / min, specifically, 1° C. / min, 2° C. / min, 3° C. / min, 5° C. / min, 6° C. / min, 8° C. / min, 10° C. / min, 12° C. / min, 14° C. / min, 16° C. / min, 18° C. / min, or 20° C. / min, and of course may be other values within the above range, but is not limited thereto. The temperature may be lowered to room temperature.
[0096] In some embodiments, the carbonization process is carried out under inert gas protection, the inert gas comprising at least one of argon, neon, helium, and krypton.
[0097] In some embodiments, the shaping treatment includes at least one of ball mill, sand mill, roller mill, stirring mill, turn mill and planetary mill. Preferably, the shaping treatment method is ball mill, and the ball mill time is 0.5h to 24h, specifically, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 8h, 12h, 16h, 18h, 20h or 24h, etc., and is not limited to the listed values. As can be seen, by performing sufficient shaping treatment, the powder particle size of the carbon material can be reduced, and the particle size of the obtained carbon material can be more uniform, and a gas diffusion layer with a flat surface and a uniform distribution of the microporous layer carbon material can be prepared.
[0098] In some embodiments, the method further comprises sieving the shaping product prior to subjecting the shaping product to the surface modification treatment.
[0099] In some embodiments, the sieving method includes one of a fixed sieve, a roller sieve, a resonating sieve, a rotary shaft sieve, a vibrating sieve, and a chain sieve, and the mesh size of the sieving is ≧400 mesh, specifically, the mesh size of the sieving is 400 mesh, 350 mesh, 300 mesh, 250 mesh, 200 mesh, 150 mesh, 100 mesh, 70 mesh, or 50 mesh, etc., and controlling the particle size of the material within the above range contributes to the formation of a gas diffusion layer with a flat surface.
[0100] In step S2, the product of the shaping treatment is subjected to a surface modification treatment in an atmosphere containing a modifying gas to obtain a carbon material.
[0101] In some embodiments, the modified gas comprises at least one of carbon dioxide, air, water vapor, oxygen, nitrogen, and ammonia.
[0102] In some embodiments, the atmosphere further comprises an inert gas, the inert gas comprising at least one of argon, neon, helium, and krypton.
[0103] In some embodiments, the volume ratio of the modified gas to the inert gas in the atmosphere is (0.5-10):10, specifically, but not limited to, 0.5:10, 1:10, 2:10, 3:10, 4:10, 5:10, 6:10, 7:10, 8:10, 9:10, or 10:10.
[0104] In some embodiments, the temperature of the surface modification treatment is 400°C to 1700°C, specifically, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1200°C, 1400°C, 1500°C, 1600°C or 1700°C, etc., but not limited thereto. Within this temperature range, it is possible to avoid the destruction of the structural characteristics of the carbon material after carbonization, and to introduce other non-carbon elements into the surface of the carbon material to perform surface modification, thereby enhancing the structural orderliness of the carbon material surface and improving the resistance to chemical and electrochemical corrosion. Preferably, the temperature of the surface modification treatment is 500°C to 1200°C.
[0105] In some embodiments, the duration of the surface modification treatment is 0.5 h to 3 h, specifically, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, or 3 h, etc., but is not limited to the listed values.
[0106] In some embodiments, the heating rate for the surface modification treatment is 2°C / min to 30°C / min, specifically, 2°C / min, 5°C / min, 7°C / min, 10°C / min, 15°C / min, 18°C / min, 20°C / min, 25°C / min or 30°C / min, etc., and is not limited to the listed values.
[0107] The present application provides a fuel cell, which includes a plurality of cell units having gas diffusion layers, the gas diffusion layers including the carbon material described above or the carbon material prepared by the preparation method described above.
[0108] The present application will be described in more detail below by dividing it into several examples. The present application is not limited to the following specific examples. As long as it does not deviate from the scope of the claims, it can be appropriately modified and implemented.
[0109] [Example 1] (1) Camphor is selected as the defect repairing agent, the camphor is put into a ball mill tank for polishing treatment, and then polished in a turn mill for 3 hours to obtain polished camphor, whose average particle size is 0.5 μm; (2) Select a carbon black material with an average particle size of 35 nm and an oil absorption of 350 mL / 100 g, and measure the carbon characteristic peak and graphite characteristic peak I of the carbon black material. D / I G = 1.53, which is 2.5 kN / cm 2 The powder conductivity under pressure is σ=10.0S / cm. The carbon black material and the ground camphor are mixed in a mixer. The mass ratio of the carbon black material to the camphor is 10:0.5. The mixing time is 1 hour. A mixed material is obtained. (3) The mixed material is placed in a graphite crucible and placed in a graphitization furnace. Under an argon atmosphere, the heating rate is controlled at 10°C / min, the temperature is raised to 1,800°C, high-temperature carbonization is performed for 1 hour, the material is cooled to room temperature, and the sample is removed. (4) The product after carbonization is transferred to a 5L ball mill tank and ground in a turn mill for 3 hours to crush the agglomerated large particle carbon material into small particle carbon material. The ground carbon material is sieved through a 100 mesh sieve, and the sieved material is heat-treated at 500°C for 2 hours in an air and argon mixed atmosphere, with the volume ratio of air to argon being 5:10, to obtain the carbon material.
[0110] The carbon material prepared in this example is composed of a plurality of carbon particles, the carbon particles are spherical, the surface of the carbon particles contains a plurality of connected carbon crystal particles, and the grain boundary density p of the surface of the carbon particles is 12.7.
[0111] [Example 2] (1) Camphor is selected as the defect repairing agent, the camphor is put into a ball mill tank for polishing treatment, and then polished in a turn mill for 3 hours to obtain polished camphor, whose average particle size is 0.5 μm; (2) Select a carbon black material with an average particle size of 35 nm and an oil absorption of 350 mL / 100 g, and measure the carbon characteristic peak and graphite characteristic peak I of the carbon black material. D / I G = 1.53, which is 2.5 kN / cm 2 The powder conductivity under pressure is σ=10.0S / cm. The carbon black material and the ground camphor are mixed in a mixer. The mass ratio of the carbon black material to the camphor is 10:0.5. The mixing time is 1 hour. A mixed material is obtained. (3) The mixed material is placed in a graphite crucible and placed in a graphitization furnace. Under an argon atmosphere, the heating rate is controlled at 10°C / min, the temperature is raised to 2200°C, and high-temperature carbonization is performed for 1 hour. The material is then cooled to room temperature, and the sample is removed. (4) The product after carbonization is transferred to a 5L ball mill tank and ground in a turn mill for 3 hours to crush the agglomerated large particle carbon material into small particle carbon material. The ground carbon material is sieved through a 100 mesh sieve, and the sieved carbon material is heat-treated at 500°C for 2 hours in an air and argon mixed atmosphere, with the volume ratio of air to argon being 5:10, to obtain the carbon material.
[0112] The carbon material prepared in this example includes a plurality of carbon particles, the carbon particles are spherical, the surface of the carbon particles includes a plurality of connected carbon crystal particles, and the grain boundary density p of the surface of the carbon particles is 8.7.
[0113] [Example 3] (1) Camphor is selected as the defect repair agent, and the camphor is put into a ball mill tank for polishing treatment, and then turned into a mill for 4 hours to obtain the camphor after polishing, and its average particle size is 1 μm; (2) Select a carbon black material with an average particle size of 35 nm and an oil absorption of 350 mL / 100 g, and measure the carbon characteristic peak and graphite characteristic peak I of the carbon black material. D / I G = 1.53, which is 2.5 kN / cm 2The powder conductivity under pressure is σ=10.0S / cm. The carbon black material and the ground camphor are mixed in a mixer. The mass ratio of the carbon black material to the camphor is 10:0.5. The mixing time is 2 hours. A mixed material is obtained. (3) The mixed material is placed in a graphite crucible and placed in a graphitization furnace. Under an argon atmosphere, the heating rate is controlled at 10°C / min, the temperature is raised to 2800°C, and high-temperature carbonization is performed for 1 hour. The material is then cooled to room temperature, and the sample is removed. (4) The product after carbonization is transferred to a 5L ball mill tank and ground in a turn mill for 3 hours to crush the agglomerated large particle carbon material into small particle carbon material. The ground carbon material is sieved through a 100 mesh sieve, and the sieved carbon material is heat-treated at 500°C for 2 hours in an air and argon mixed atmosphere, with the volume ratio of air to argon being 5:10, to obtain the carbon material.
[0114] The carbon material prepared in this example includes a plurality of carbon particles, the carbon particles are spherical, the surface of the carbon particles includes a plurality of connected carbon crystal particles, and the grain boundary density p of the surface of the carbon particles is 4.4.
[0115] [Example 4] (1) Quinoline is selected as a defect repair agent, and the quinoline is put into a ball mill tank for polishing, and then polished in a turn mill for 6 hours to obtain polished quinoline, whose average particle size is 0.5 μm; (2) Select a carbon black material with an average particle size of 35 nm and an oil absorption of 350 mL / 100 g, and measure the carbon characteristic peak and graphite characteristic peak I of the carbon black material. D / I G = 1.53, which is 2.5 kN / cm 2 The powder conductivity under pressure is σ=10.0S / cm. The carbon black material and the ground quinoline are mixed in a mixer. The mass ratio of the carbon black material to the quinoline is 10:0.1. The mixing time is 2 hours. A mixed material is obtained. (3) The mixed material is placed in a graphite crucible and placed in a graphitization furnace. Under an argon atmosphere, the heating rate is controlled at 10°C / min, the temperature is raised to 3000°C, and high-temperature carbonization is performed for 1 hour. The material is then cooled to room temperature, and the sample is removed. (4) The product after the carbonization treatment is transferred to a 5L ball mill tank and ground in a turn mill for 3 hours to crush the agglomerated large particle carbon material into small particle carbon material. The ground carbon material is sieved through a 100 mesh sieve. The sieved carbon material is heat-treated at 500°C for 2 hours in an air and argon mixed atmosphere, with the volume ratio of air to argon being 5:10, to obtain the carbon material.
[0116] The carbon material prepared in this example includes a plurality of carbon particles, the carbon particles are spherical, the surface of the carbon particles includes a plurality of connected carbon crystal particles, and the grain boundary density p of the surface of the carbon particles is 4.3.
[0117] [Example 5] (1) Styrene is selected as the defect repair agent, and the styrene is put into a ball mill tank for polishing, and then polished in a turn mill for 2 hours to obtain polished styrene, whose average particle size is 0.5 μm; (2) Select a carbon black material with an average particle size of 35 nm and an oil absorption of 350 mL / 100 g, and measure the carbon characteristic peak and graphite characteristic peak I of the carbon black material. D / I G = 1.53, which is 2.5 kN / cm 2 The powder conductivity under pressure is σ=10.0S / cm. The carbon black material and the ground styrene are mixed in a mixer. The mass ratio of the carbon black material to the styrene is 10:1. The mixing time is 3 hours. A mixed material is obtained. (3) The mixed material is placed in a graphite crucible and placed in a graphitization furnace. Under an argon atmosphere, the heating rate is controlled at 10°C / min, the temperature is raised to 2800°C, and high-temperature carbonization is performed for 1 hour. The material is then cooled to room temperature, and the sample is removed. (4) The product after carbonization is transferred to a sand mill and sand milled for 5 hours to crush the agglomerated large particle carbon material into small particle carbon material, and the polished carbon material is sieved through a 100 mesh sieve. The sieved carbon material is heat-treated at 400°C for 2 hours in a mixed atmosphere of water vapor and argon, with a volume ratio of water vapor to argon of 5:10, to obtain the carbon material.
[0118] The carbon material prepared in this example includes a plurality of carbon particles, the carbon particles are spherical, the surface of the carbon particles includes a plurality of connected carbon crystal particles, and the grain boundary density p of the surface of the carbon particles is 4.8.
[0119] [Example 6] (1) Phenol is selected as a defect repair agent, and the phenol is put into a ball mill tank for polishing treatment, and then polished in a turn mill for 3 hours to obtain polished phenol, whose average particle size is 0.8 μm; (2) Select a carbon black material with an average particle size of 35 nm and an oil absorption of 350 mL / 100 g, and measure the carbon characteristic peak and graphite characteristic peak I of the carbon black material. D / I G = 1.53, which is 2.5 kN / cm 2 The powder conductivity under pressure is σ=10.0S / cm. The carbon black material and the ground phenol are mixed in a mixer. The mass ratio of the carbon black material to the phenol is 10:2. The mixing time is 1.5 hours. A mixed material is obtained. (3) The mixed material is placed in a graphite crucible and placed in a graphitization furnace. Under an argon atmosphere, the heating rate is controlled at 10°C / min, the temperature is raised to 2800°C, and high-temperature carbonization is performed for 1 hour. The material is then cooled to room temperature, and the sample is removed. (4) The product after carbonization is transferred to a 5L ball mill tank and ground in a turn mill for 3 hours to crush the agglomerated large particle carbon material into small particle carbon material. The ground carbon material is sieved through a 100 mesh sieve, and the sieved material is heat-treated at 800°C for 2 hours in a mixed atmosphere of ammonia and argon, with a volume ratio of ammonia to argon being 5:10, to obtain the carbon material.
[0120] The carbon material prepared in this example includes a plurality of carbon particles, the carbon particles are spherical, the surface of the carbon particles includes a plurality of connected carbon crystal particles, and the grain boundary density p of the surface of the carbon particles is 4.6.
[0121] [Example 7] (1) Camphor is selected as the defect repairing agent, the camphor is put into a ball mill tank for polishing, and then polished in a turn mill for 4 hours to obtain polished camphor, whose average particle size is 1 μm; (2) Select a carbon black material with an average particle size of 35 nm and an oil absorption of 350 mL / 100 g, and measure the carbon characteristic peak and graphite characteristic peak I of the carbon black material. D / I G = 1.53, which is 2.5 kN / cm 2 The powder conductivity under pressure is σ=10.0S / cm. The carbon black material and the ground camphor are mixed in a mixer. The mass ratio of the carbon black material to the camphor is 10:0.05. The mixing time is 2 hours. A mixed material is obtained. (3) The mixed material is placed in a graphite crucible and placed in a graphitization furnace. Under an argon atmosphere, the heating rate is controlled at 10°C / min, the temperature is raised to 2800°C, and high-temperature carbonization is performed for 1 hour. The material is then cooled to room temperature, and the sample is removed. (4) The product after carbonization is transferred to a 5L ball mill tank and ground in a turn mill for 3 hours to crush the agglomerated large particle carbon material into small particle carbon material. The ground carbon material is sieved through a 100 mesh sieve, and the sieved carbon material is heat-treated at 500°C for 2 hours in an air and argon mixed atmosphere, with the volume ratio of air to argon being 5:10, to obtain the carbon material.
[0122] The carbon material prepared in this example comprises secondary particles, the secondary particles comprising a plurality of carbon particles, the carbon particles being spherical, the surfaces of the carbon particles comprising a plurality of connected carbon crystal particles, and the grain boundary density p of the surfaces of the carbon particles being 6.2.
[0123] [Example 8] (1) Camphor is selected as the defect repairing agent, and the camphor is put into a ball mill tank for polishing treatment, and then ball milled for 4 hours to obtain polished camphor, whose average particle size is 50 nm; (2) Select a carbon black material with an average particle size of 35 nm and an oil absorption of 350 mL / 100 g, and measure the carbon characteristic peak and graphite characteristic peak I of the carbon black material. D / I G = 1.53, which is 2.5 kN / cm 2The powder conductivity under pressure is σ=10.0S / cm. The carbon black material and the ground camphor are mixed in a mixer. The mass ratio of the carbon black material to the camphor is 10:0.5. The mixing time is 2 hours. A mixed material is obtained. (3) The mixed material is placed in a graphite crucible and placed in a graphitization furnace. Under an argon atmosphere, the heating rate is controlled at 10°C / min, the temperature is raised to 2800°C, and high-temperature carbonization is performed for 1 hour. The material is then cooled to room temperature, and the sample is removed. (4) The product after carbonization is transferred to a 5L ball mill tank and ground in a turn mill for 3 hours to crush the agglomerated large particle carbon material into small particle carbon material. The ground carbon material is sieved through a 100 mesh sieve, and the sieved carbon material is heat-treated at 500°C for 2 hours in an air and argon mixed atmosphere, with the volume ratio of air to argon being 5:10, to obtain the carbon material.
[0124] The carbon material prepared in this example includes a plurality of carbon particles, the carbon particles are spherical, the surface of the carbon particles includes a plurality of connected carbon crystal particles, and the grain boundary density p of the surface of the carbon particles is 5.7.
[0125] [Example 9] This is similar to Example 3, except for the following points: no defect repair agent was added.
[0126] [Example 10] (1) Camphor is selected as the defect repairing agent, the camphor is put into a ball mill tank for polishing, and then polished in a turn mill for 4 hours to obtain polished camphor, whose average particle size is 1 μm; (2) Select a carbon black material with an average particle size of 35 nm and an oil absorption of 350 mL / 100 g, and measure the carbon characteristic peak and graphite characteristic peak I of the carbon black material. D / I G = 1.53, which is 2.5 kN / cm 2 The powder conductivity under pressure is σ=10.0S / cm. The carbon black material and the ground camphor are mixed in a mixer. The mass ratio of the carbon black material to the camphor is 10:0.5. The mixing time is 2 hours. A mixed material is obtained. (3) The mixed material is placed in a graphite crucible and placed in a graphitization furnace. Under an argon atmosphere, the heating rate is controlled at 10°C / min, the temperature is raised to 2800°C, and high-temperature carbonization is performed for 1 hour. The material is then cooled to room temperature, and the sample is removed.
[0127] [Comparative Example 1] Select a carbon black material with an average particle size of 35 nm and an oil absorption of 350 mL / 100 g. The carbon characteristic peak and graphite characteristic peak I of the carbon black material were measured. D / I G = 1.53, which is 2.5 kN / cm 2 Carbon black material having a powder electrical conductivity of σ=10.0 S / cm under pressure is used as the carbon material.
[0128] [Comparative Example 2] Select a carbon black material with an average particle size of 36 nm and an oil absorption of 320 mL / 100 g. The carbon characteristic peak and graphite characteristic peak I of the carbon black material were measured. D / I G = 1.46, which is 2.5 kN / cm 2 Carbon black material XC72 with a carbon material powder conductivity under pressure of σ=12.9 S / cm is used as the carbon material.
[0129] [Comparative Example 3] A multi-walled carbon nanotube with a length of 15 μm and a diameter of 15 nm was selected and subjected to a load of 2.5 kN / cm 2 Carbon material powder under pressure Multi-walled carbon nanotubes with electrical conductivity σ=25.6 S / cm are used as the carbon material.
[0130] [Comparative Example 4] 2.5kN / cm 2 Carbon material powder under pressure Single-layer graphene with electrical conductivity σ = 27.8 S / cm is used as the carbon material.
[0131] [measurement] 1)Method of measuring particle size of carbon materials: For particle size measurement methods, refer to GB / T 19077-2016. Measurements can be easily performed using a laser particle size analyzer such as the Mastersizer 3000 laser particle size analyzer from Malvern Instruments, UK.
[0132] 2)Measuring method for the specific surface area of carbon materials: The amount of gas adsorbed on the solid surface is measured by changing the relative pressure at constant temperature and low temperature, and then the amount of sample monolayer adsorption is calculated based on the Brownor-Emmett-Taylor adsorption theory and its equation (BET equation), and the specific surface area of the material is calculated.
[0133] 3) Measurement method for average particle size La of carbon crystal particles and grain boundary density: 20 parts (10 g / part) of carbon powder particles were randomly taken and measured by Raman spectroscopy (Raman laser wavelength λ = 514 nm). The peak area I of the carbon characteristic peak of the carbon particles was D and the peak area of the graphite characteristic peak I G Ratio I D / I G The value of R n where n = 1, 2, 3…20, I of 20 parts of carbon particles D / I G The average value of is R, The average particle size of the carbon crystal particles is La=4.4 / R. Grain boundary density
number
[0134] 4) Crystal surface spacing d 002 Measurement method: The diffraction angle position of the C{002} crystal plane measured by XRD powder diffraction is given by the Bragg equation 2d 002 Sinθ=λK, the {002} crystal surface spacing of the carbon material, d 002 get.
[0135] 5) Method for measuring particle shape and carbon crystal particle shape: The appearance of the carbon particles is measured by atomic force microscopy (AFM) and high-magnification transmission electron microscopy (HRTEM).
[0136] 6) Porosity measurement method: The porosity can be measured by referring to GB / T 21650-2008, and can be easily measured by a mercury piezoelectric meter.
[0137] 7) Powder contact angle measurement method: The powder is placed in a powder tank and pressed firmly, and the contact angle of the carbon powder material is measured using a contact angle tester.
[0138] 8) Oil absorption measurement method: Linseed kernel oil is added dropwise at a constant rate to unmodified carbon material and modified carbon material powders, and a rotor is used to stir the powders. An increase in the amount of linseed kernel oil results in an increase in the viscosity of the mixture, and the oil absorption is the amount of linseed kernel oil at which the viscosity change produced by the torque reaches a maximum torque of 70% of the torque added to the resulting carbon material powder.
[0139] 9)Measuring method for material powder conductivity: Using a resistivity tester (Suzhou Jeong Electronics ST-2255A), take a 5g powder sample, apply a constant pressure of 5000kg ± 2kg with an electronic press and maintain it for 15 to 25 seconds. The sample is placed between the electrodes of the tester. The height of the sample is h (cm), the voltage across both ends is U, the current is I, and the resistance is R (KΩ). The area after powder pressing is S = 3.14 cm 2 The powder conductivity was calculated by the formula δ=h / (S*R) / 1000, and the unit is S / cm.
[0140] 10) Battery performance measurement method: The performance of a single cell having a gas diffusion layer prepared from a carbon material was measured using a battery measurement stand. The anode catalyst loading of the membrane electrode used was 0.1 mg cm -2 , cathode catalyst loading 0.4 mg cm -2 , battery operating temperature 80℃, humidity 100RH%, battery back pressure 150kPa / 150kPa. 2A / cm 2 The cell voltage of the cell under the current density is recorded.
[0141] 11)Battery internal resistance method: 2A / cm 2 The internal resistance of the single cell was measured by high-frequency impedance using an electrochemical impedance meter under a current density of 5 kHz AC signal. The performance measurement results were as follows:
[0142] [Table 1]
[0143] As can be seen from the measurement data of Examples 1 to 10, the carbon material prepared by the above method has a smaller grain boundary density between carbon crystal particles on the surface of the carbon material particles, and the number of sites on the surface of the carbon particles that are prone to corrosion is reduced, which effectively improves the service life of the carbon material. The smaller the surface grain boundary density of the carbon particles, the better the hydrophobicity, and the less likely the moisture generated by the reaction is to collect in the pores of the carbon material, which can maintain the gas conduction ability of the pore structure of the microporous layer made of this material, and improve the battery performance under conditions of high humidity and large current density. In addition, the carbon material can achieve both high electrical conductivity and high graphitization degree. The higher the electrical conductivity performance of similar carbon materials and the stronger the electron transport performance of the carbon material, the smaller the battery internal resistance, the lower the power loss, and the lower the σ / d of the carbon material. 002 ≧3*10 8 S / cm 2 (0.338 nm ≤ d 002 ≦0.345nm), the resulting cell was 2A / cm 2 The operating voltage under high current density is higher than 0.57V, which is 30mV higher than the battery voltage of other carbon materials, and the corresponding battery output power is also larger. The higher the graphitization degree of the carbon material, the higher the corrosion resistance of the material. Under high current density, the gas diffusion layer made of this material has high electrochemical conversion efficiency and long service life.
[0144] As shown in FIG. 4, from the thermal weight loss diagrams of the carbon materials of Examples 1, 3 and Comparative Example 1, the carbon material of Comparative Example 1 rapidly decomposes in the range of 600°C to 700°C, and its thermal stability is significantly lower than that of Examples 1 or 3.
[0145] As shown in Fig. 5, the electrochemical constant-potential polarization curves of the gas diffusion layers of the fuel cells prepared by coating with the carbon materials of Examples 1 and 3 and Comparative Example 1 are used to simulate the reverse electrode state of the fuel cell to measure the resistance of the carbon materials to electrochemical corrosion. The electrochemical stability of the gas diffusion layers prepared by coating with the carbon materials of Examples 1 and 3 and Comparative Example 1 as the microporous carbon layer is measured by constant-potential polarization measurement under a voltage of 2V (vs. RHE). As can be seen from the measurement results of Fig. 5, the electrochemical stability of Examples 1 and 3 treated at high temperature is significantly higher than that of Comparative Example 1.
[0146] 6 is a linear graph of the corrosion current growth rate of the corresponding carbon materials obtained by linear fitting of the electrochemical constant-potential polarization curves of the diffusion layers prepared with the carbon material coatings of Examples 1 and 3 and Comparative Example 1 of the present application. Among them, the corrosion current growth rate of Example 1 is 1.52 μA / (cm 2 *h), and the corrosion current growth rate of Example 3 was 0.68 μA / (cm 2 *h), and the corrosion current growth rate of Comparative Example 1 was 2.55 μA / (cm 2 *h), and the corrosion current growth rate of a carbon material is proportional to the grain boundary density of the material, and the higher the grain boundary density of the material, the more sites are susceptible to corrosion, and the more rapidly the carbon material is corroded. Preferably, a microporous layer carbon material having high durability should have a low grain boundary density, p, where p is 1≦p≦6.5.
[0147] Compared with Example 3, in Example 7, the content of the defect repair agent added is too small, and the defect repair on the surface of the carbon particles is insufficient, and the grain boundary density of the carbon particles is significantly increased compared to Example 3. It can be seen that an appropriate defect repair agent can sufficiently repair the surface defects of carbon particles and prepare carbon particles with a lower grain boundary density.
[0148] Compared with Example 3, in Example 8, the particle size of the added defect repair agent is too small to effectively repair the defects on the surface of the carbon particles, and the grain boundary density of the carbon particles is significantly increased compared to Example 3. It can be seen that an appropriate particle size of the defect repair agent can effectively repair the surface defects of carbon particles and prepare carbon particles with a smaller grain boundary density.
[0149] Compared with Example 3, in Example 9, the defect repairing agent is not added, and the surface of the carbon black material cannot be sufficiently deposited to form a laminated carbon layer, and the grain boundary density on the surface of the carbon particles is significantly increased compared to Example 3, so that when the battery is operated for a long time, carbon corrosion is likely to occur, the internal resistance of the battery increases, and the service life of the battery is shortened. As can be seen from this, the defect repairing agent used in Example 3 can be sufficiently deposited on the surface of the carbon black material to form a laminated carbon layer, effectively repair the surface defects of the carbon particles, and prepare carbon particles with a smaller grain boundary density.
[0150] Compared with Example 3, in Example 10, the carbon material is not treated with modified gas, but with oxidizing gas at medium and low temperatures, so that the highly volatile part of the repair agent and carbon black material can be vaporized at high temperature to eliminate the amorphous carbon deposited on the carbon surface. The grain boundary density of the carbon crystal particles is significantly increased compared to Example 3, the electrical conductivity is significantly decreased, the porosity and specific surface area are slightly decreased, and when the battery is operated for a long time, carbon corrosion is likely to occur, the internal resistance of the battery increases, and the service life of the battery is reduced. As can be seen from this, the oxidizing gas used in Example 3 can effectively remove the amorphous structure on the surface of the carbon particles, and prepare carbon particles with smaller grain boundary density and higher electrical conductivity.
[0151] Comparative Examples 1 and 2 are existing commonly used microporous carbon materials, which show good performance in fuel cells. However, the grain boundary density p value of the carbon black material is large, and there are many corrosion sites. When the battery is operated for a long period of time, the carbon black material deteriorates rapidly under operating environments that are prone to carbon corrosion, such as reverse polarity and acidic high oxygen, and the overall service life is shortened.
[0152] In Comparative Example 3, multi-walled carbon nanotubes having a length of 15 μm and a diameter of 15 nm are used as the carbon material. Multi-walled carbon nanotubes have higher electrical conductivity and corrosion resistance than carbon black. The gas diffusion layer prepared by coating with this nano-carbon material is prone to forming a stacked structure of tubular clusters that leads to uneven coating. The battery assembled using this gas diffusion layer has high electron transfer performance under low current density, but as the current density increases, the internal resistance of the battery increases and the mass transfer performance of the battery decreases.
[0153] In Comparative Example 4, single-layer ordered graphene is selected. Single-layer graphene has a two-dimensional planar structure with good crystallinity, high corrosion resistance, and high electron transport performance. However, due to its lamellar structure, the stacked lamellae block the pore structure of the substrate, significantly restricting the transport of water and gas during the reaction. The performance of the gas diffusion layer prepared using single graphene as a microporous carbon material rapidly declines with increasing power density, increasing the internal resistance of the battery and reducing the mass transport performance of the battery.
[0154] Although the present application discloses preferred embodiments as described above, it is not intended to limit the scope of the claims, and a person skilled in the art can make various changes and modifications without departing from the concept of the present application, and therefore the scope of protection of the present application shall be subject to the claims of the present application.
[0155] (Additional Note) (Appendix 1) A carbon material, comprising carbon particles, a surface of the carbon particles being composed of a plurality of connected carbon crystal particles, and a grain boundary being present between two adjacent carbon crystal particles; the grain boundary density p on the surface of the carbon particle is 1≦p≦15; The grain boundary density is determined by the following measurement method: 20 pieces of carbon powder particles were randomly taken and measured by Raman spectroscopy. The peak area of the carbon characteristic peak of the carbon powder particles was I D and the peak area of the graphite characteristic peak I G Ratio I D / I G The value of R n where n=1, 2, 3…20, I of 20 parts of carbon powder particles D / I G The average value of is R, Grain boundary density
number
[0156] (Appendix 2) The carbon material has at least one of the following characteristics: (1) the carbon particles are spherical or nearly spherical; (2) the average particle diameter D of the carbon particles is 20 nm≦D≦200 nm; (3) the carbon crystal particles are formed by laminating carbon layers; (4) the average particle size La of the carbon crystal particles is 3 nm≦La≦30 nm; (5) The carbon material according to appended claim 1, wherein a grain boundary density p on the surface of the carbon particle satisfies 1≦p≦6.5.
[0157] (Appendix 3) As a result of the powder X-ray diffraction test, the crystal surface spacing of the graphite phase {002} of the carbon material was d 002 nm, 2.5 kN / cm 2 The powder conductivity of the carbon material under pressure is σS / cm, and σ / d 002 ≧2*10 8 S / cm 2 2. The carbon material according to claim 1,
[0158] (Appendix 4) The carbon material has at least one of the following characteristics: (1) The crystal surface spacing of the graphite phase {002} of the carbon material is d 002 nm, and 0.338≦d 002 ≦0.345, (2) 2.5 kN / cm 24. The carbon material according to claim 3, wherein the powder conductivity of the carbon material under pressure is σS / cm and σ≧7.
[0159] (Appendix 5) The carbon material has at least one of the following characteristics: (1) The porosity of the carbon material is ≧60%, (2) the powder contact angle of the carbon material is 120° to 155°; (3) The specific surface area of the carbon material is 30 m 2 / g~250m 2 / g, (4) the oil absorption of the carbon material is 100 mL / 100 g to 450 mL / 100 g; (5) The carbon material according to any one of claims 1 to 4, wherein the carbon material has an average particle size of 0.1 μm to 10 μm.
[0160] (Appendix 6) A method for preparing a carbon material, comprising the steps of: A step of carbonizing the mixed material containing the carbon black material and the defect repair agent at 1800 ° C to 3000 ° C and then performing a shaping process; and performing a surface modification treatment on the product of the shaping treatment in an atmosphere containing a modifying gas to obtain the carbon material.
[0161] (Appendix 7) The method has at least one of the following characteristics: (1) The boiling point of the defect repairing agent is 50°C to 400°C, (2) the defect repair agent comprises a volatile organic compound and / or a semi-volatile organic compound; (3) the defect repair agent includes a volatile organic compound, the volatile organic compound includes at least one of camphor, phenol, o-phthalaldehyde, isophthalaldehyde, terephthalaldehyde, p-benzoquinone, benzoic acid, palmitol, aminoquinoline, and naphthalene; (4) The defect repair agent includes a semi-volatile organic compound, and the semi-volatile organic compound includes at least one of benzenediol, phthalic acid, isophthalaldehyde, and anthracene; (5) Before subjecting the mixed material containing the carbon black material and the defect repairing agent to a carbonization treatment at 1800 ° C. to 3000 ° C., the method further includes a step of shaping the defect repairing agent, and mixing the shaped repairing agent and the carbon black material to obtain a mixed material; (6) The average particle size of the defect repairing agent is 0.1 μm to 1 μm, (7) A mass ratio of the carbon black material to the defect repairing agent is 10:(0.1 to 2), (8) The carbon black material has an average particle size of 20 nm to 200 nm, (9) the oil absorption of the carbon black material is 100 mL / 100 g to 450 mL / 100 g; (10) When measured by Raman spectroscopy, the carbon black material has a carbon characteristic peak I D and graphite characteristic peak I G I D / I G ≦2.0, (11) 2.5 kN / cm 2 7. The process of claim 6, wherein the powder conductivity of the carbon black material at pressure is σ≧8 S / cm.
[0162] (Appendix 8) The method has at least one of the following characteristics: (1) The carbonization treatment time is 0.1 h to 3 h, (2) The temperature rise rate of the carbonization treatment is 2°C / min to 30°C / min, (3) the carbonization process is carried out under inert gas protection, the inert gas comprising at least one of argon, neon, helium and krypton; (4) The shaping treatment includes at least one of a ball mill, a sand mill, a roller mill, an agitation mill, a turn mill, and a planetary mill; (5) The preparation method described in Appendix 6, characterized in that the method further comprises a step of sieving the shaping product before subjecting the shaping product to a surface modification treatment.
[0163] (Appendix 9) The method has at least one of the following characteristics: (1) the modified gas includes at least one of carbon dioxide, air, water vapor, oxygen, nitrogen, and ammonia; (2) the atmosphere further comprises an inert gas, the inert gas comprising at least one of argon, neon, helium, and krypton; (3) the volume ratio of the modified gas to the inert gas in the atmosphere is (0.5 to 10):10; (4) The temperature of the surface modification treatment is 400°C to 1700°C, and preferably 500°C to 1200°C; (5) The method according to any one of claims 6 to 8, wherein the temperature increase rate in the surface modification treatment is 2°C / min to 30°C / min.
[0164] (Appendix 10) A fuel cell comprising a plurality of cell units each having a gas diffusion layer, the gas diffusion layer comprising the carbon material according to any one of Appendices 1 to 5 or the carbon material prepared by the preparation method according to any one of Appendices 6 to 9.
Claims
1. A carbon material, comprising carbon particles, a surface of the carbon particles being composed of a plurality of connected carbon crystal particles, and a grain boundary being present between two adjacent carbon crystal particles; The grain boundary density p of the surface of the carbon particle is 1≦p≦15, The grain boundary density is determined by the following measurement method: 20 parts (10 g / part) of carbon particles were randomly obtained and measured by Raman spectroscopy. The peak area I D and the peak area of the graphite characteristic peak I G Ratio I D / I G The value of R n where n=1, 2, 3...20, and the I of 20 parts of carbon particles D / I G The average value of is R, Grain boundary density [0010] and A carbon material, wherein D is an average particle diameter of the carbon particles.
2. The carbon material has at least one of the following characteristics: (1) the carbon particles are spherical or nearly spherical; (2) The average particle diameter D of the carbon particles is 20 nm≦D≦200 nm; (3) The carbon crystal particles are formed by stacking carbon layers, (4) The average particle size La of the carbon crystal particles is 3 nm≦La≦30 nm, (5) The carbon material according to claim 1, characterized in that the grain boundary density p on the surface of the carbon particle is 1≦p≦6.
5.
3. As a result of a powder X-ray diffraction test, the crystal surface spacing of the graphite phase {002} of the carbon material was d 002 nm, 2.5 kN / cm 2 The powder conductivity of the carbon material under pressure is σS / cm, and σ / d 002 ≧2*10 8 S / cm 2 The carbon material according to claim 1,
4. The carbon material has at least one of the following characteristics: (1) The crystal surface spacing of the graphite phase {002} of the carbon material is d 002 nm, and 0.338≦d 002 ≦0.345, (2) 2.5kN / cm 2 4. The carbon material according to claim 3, wherein the powder conductivity of the carbon material under pressure is σS / cm and σ≧7.
5. The carbon material has at least one of the following characteristics: (1) The porosity of the carbon material is ≧60%, (2) the powder contact angle of the carbon material is 120° to 155°; (3) The specific surface area of the carbon material is 30 m 2 / g~250m 2 / g, (4) the oil absorption of the carbon material is 100 mL / 100 g to 450 mL / 100 g; (5) The carbon material according to any one of claims 1 to 4, characterized in that the average particle size of the carbon material is 0.1 µm to 10 µm.
6. A method for producing the carbon material according to claim 1, comprising the steps of: A step of carbonizing the mixed material containing the carbon black material and the defect repair agent at 1800°C to 3000°C and then performing a shaping process; and performing a surface modification treatment on the shaping treatment product in an atmosphere containing a modification gas to obtain the carbon material. The method for producing a carbon material is characterized in that the defect repair agent decomposes during the carbonization treatment and precipitates on the surface of the carbon particles to repair defects on the surface of the carbon particles, thereby obtaining carbon particles having a lower grain boundary density on the surface, and the shaping treatment reduces the particle size of the carbon particles and / or makes the particle size of the carbon particles more uniform.
7. The method has at least one of the following characteristics: (1) The boiling point of the defect repairing agent is 50° C. to 400° C., (2) the defect repair agent includes a volatile organic compound and / or a semi-volatile organic compound; (3) The defect repair agent includes a volatile organic compound, and the volatile organic compound includes at least one of camphor, phenol, o-phthalaldehyde, isophthalaldehyde, terephthalaldehyde, p-benzoquinone, benzoic acid, palmitol, aminoquinoline, and naphthalene; (4) The defect repair agent includes a semi-volatile organic compound, and the semi-volatile organic compound includes at least one of benzenediol, phthalic acid, isophthalaldehyde, and anthracene; (5) Before subjecting the mixed material containing the carbon black material and the defect repairing agent to a carbonization treatment at 1800 ° C. to 3000 ° C., the method further includes a step of shaping the defect repairing agent, and mixing the shaped repairing agent and the carbon black material to obtain a mixed material; (6) The average particle size of the defect repair agent is 0.1 μm to 1 μm, (7) A mass ratio of the carbon black material to the defect repair agent is 10:(0.1 to 2), (8) The carbon black material has an average particle size of 20 nm to 200 nm, (9) The oil absorption of the carbon black material is 100 mL / 100 g to 450 mL / 100 g, (10) When measured by Raman spectroscopy, the carbon black material has a carbon characteristic peak I D and graphite characteristic peak I G and I D / I G ≦2.0, (11) 2.5kN / cm 2 7. The process according to claim 6, wherein the powder conductivity of the carbon black material at pressure σ ≥ 8 S / cm.
8. The method has at least one of the following characteristics: (1) The carbonization treatment time is 0.1 h to 3 h, (2) The temperature increase rate of the carbonization treatment is 2° C. / min to 30° C. / min, (3) the carbonization process is carried out under inert gas protection, the inert gas comprising at least one of argon, neon, helium and krypton; (4) The shaping treatment includes at least one of a ball mill, a sand mill, a roller mill, an agitation mill, a turn mill, and a planetary mill; (5) The method according to claim 6, characterized in that the method further comprises a step of sieving the shaping product before subjecting the shaping product to a surface modification treatment.
9. The method has at least one of the following characteristics: (1) The modified gas includes at least one of carbon dioxide, air, water vapor, oxygen, nitrogen, and ammonia; (2) the atmosphere further comprises an inert gas, the inert gas comprising at least one of argon, neon, helium, and krypton; (3) the volume ratio of the modified gas to the inert gas in the atmosphere is (0.5 to 10):10; (4) The temperature of the surface modification treatment is 400° C. to 1700° C., and the temperature of the surface modification treatment is preferably 500° C. to 1200° C.; (5) The method according to any one of claims 6 to 8, characterized in that the temperature increase rate in the surface modification treatment is 2°C / min to 30°C / min.
10. A fuel cell comprising a plurality of cell units each having a gas diffusion layer, the gas diffusion layer comprising the carbon material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Graphite cathode material for lithium ion battery and preparation method thereof
CN102117911A
Komitsudokokuenseikeitai no seizoho
JP1976026912A
Negative electrode active material for lithium secondary battery and lithium secondary battery using the same as negative electrode active material
JP2000123835A
Preparation of graphitized carbon black
JP2000273351A
Negative electrode active material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
JP2023062531A